Effect of ARB process on textural evolution and its comparison with normal rolled AA7005 aluminum alloy - Hu, Xie; Wang, Ming Pu; Chen, Wei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Abstract: In the present work, texture evolution of AA7005 aluminum alloy during the accumulative roll bonding and conventionally rolled was investigated by X-ray diffraction. It had been found that the dominant texture components of both samples were Brass, Copper, Rotated Cube and Goss components, but the ARB texture evolution showed more quickly and complex feature. When the number of ARB cycle increased, the intensity of texture components decreased at the second and third pass, then enhanced at the fourth pass, and finally decreased. With the ARB continued there was a texture transition at the second and third pass from Brass and S to Rotated Cube components because the shear texture which form in the surface region should be put into the center during the next pass. The texture intensity enhanced at the fourth pass might be attributed to the formation of nano shear bands. The texture intensity decreasing at final cycle was correlated to redundant shear strain and continuous recrystallization during high ARB passes.